Structural model for predicting disturbance behaviour intention of Malaysian birdwatchers towards birds - Jafarpour, Marjan (2016)
Bird-watching has a range of potentially negative and positive effects on birds. The premise of this research is to mitigate negative effects of Malaysian birdwatchers with identifying the key factors influencing human behaviour towards birds in the context of recreational disturbance to help in developing a sustainable tourism. This study also developed and tested a structural model to examine influencing factors on the intention of Malaysian birdwatchers toward disturbance behaviour on birds.The main assumptions of Theory of Planned Behaviour (TPB), the theory of normative conduct and the cognitive hierarchy model were integrated into a comprehensive model. The main goal of the model was to identify key predictors that influence the intentions of Malaysian birdwatchers toward disturbance behaviour on birds.The census technique was applied to collect data from 421 Malaysian birdwatchers using a field survey. The model was tested using Structural Equation Modelling (SEM), particularly Partial Least Squares (PLS) approach in the domain of disturbance behaviour on birds to examine the direct and mediating effects of the hypotheses. SEM-PLS, a more recent approach in analysing moderating effects,was applied as an alternative analysis to further extend the body of research. Outer weights in formatively measured constructs were the results of partial regression in this study using Smart-PLS. In addition, this research helped to produce a more inclusive picture of negative effects (disturbance behaviour) of Malaysian birdwatchers in the formative structure of a developed questionnaire.Results support the hypothesised relationships (H1-H8): H1. Value orientation predicts attitude toward disturbance behaviour on birds among Malaysian birdwatchers.H2. Value orientation predicts intention toward disturbance behaviour on birds among Malaysian birdwatchers.H3. Attitude predicts intention toward disturbance behaviour on birds among Malaysian birdwatchers.H4. Subjective norm predicts intention toward disturbance behaviour on birds among Malaysian birdwatchers.H5. Descriptive norm predicts intention toward disturbance behaviour on birds among Malaysian birdwatchers. H6. Past behaviour predicts perceived behavioural control toward disturbance behaviour on birds among Malaysian birdwatchers. H7. Past behaviour predicts intention toward disturbance behaviour on birds among Malaysian birdwatchers. H8. Perceived behavioural control predicts intention toward disturbance behaviour on birds among Malaysian birdwatchers.The results also show that disturbance behavioural intentions were influenced by descriptive norms, subjective norms, past behaviour, value orientations, perceived behavioural control and attitude. From the path coefficient view, the effect of predictors on intentions towards disturbance behaviour on birds was as follows in decreasing order: descriptive norms (β=0.222), subjective norms (β=0.219), past behaviour (β=0.202), value orientation (β=0.148), perceived behavioural control (β=0.128), and attitude (β=0.123). These findings showed that subjective norms had the strongest effect on intention and, on the other hand, attitude and perceived behavioural control have the weakest effects on intention. The findings also showed that subjective norms had the strongest f2 effect size (variance) among other predictors of the model of study, but attitude and perceived behavioural control had the smallest f2 effect size on intention in the model of study. The results also supported mediating hypothesised relationships (H9 and H10): H9. Attitude mediates the relationship between value orientation and intention. H10. Perceived behavioural control mediates the relationship between past behaviour and intention. However, from the six hypotheses, all were rejected except H11 and H15; H1. The frequency of participation moderates the relationship between value orientation and intention, and H15. The frequency of participation moderates the relationship between attitude and intention. This research made several theoretical and practical contributions and provided further insight into the negative effects of Malaysian birdwatchers on birds. Theoretical, managerial and methodological implications were discussed, and several potential avenues for future research were identified.In short, greater engagement with these theories advocates better integrating social science into wildlife studies and improving the understanding and management of the interaction between recreation needs and conservation.